Susceptibility of helminth species parasites of sheep and goats to different chemical compounds in Brazil - Bichuette, Murilo Abud [UNESP]; Lopes, Welber Daniel Zanetti [UNESP]; Gomes, Lucas Vinicius Costa [UNESP]; Felippelli, Gustavo [UNESP]; Cruz, Breno Cayeiro [UNESP]; Maciel, Willian Giquelin [UNESP]; Teixeira, Weslen Fabricio Pires [UNESP]; Buzzulini, Carolina [UNESP]; Prando, Luciana [UNESP]; Soares, Vando Edésio [UNESP]; Campos, Gabriel Pimentel [UNESP]; da Costa, Alvimar José [UNESP] (Elsevier, 2015)
A total of 160 sheep and 160 goats were necropsied to evaluate the degrees of susceptibility or resistance of different helminth species to 0.2 mg/kg ivermectin (subcutaneous route), 0.2 mg/kg moxidectin (subcutaneous route), 100 mg/kg trichlorfon (administered orally) and the combination of 5 mg/kg albendazole + 7.5 mg/kg levamizole + 0.2 mg/kg ivermectin (administered orally). To achieve this objective, eight experiments were performed, four with each animal species. In each experiment, naturally infected sheep or goats were divided into five groups with eight individuals each, as follows: T01, untreated control; T02, trichlorfon; T03, ivermectin; T04, moxidectin; and T05, albendazole + levamizole + ivermectin, based on average counts of eggs per gram of feces (EPG) before treatment (experimental dates -3, -2 and -1). Seven days post-treatment (DPT), all animals were euthanized and necropsied for the recovery of helminth burdens. Based on the obtained results, it is possible to conclude that the resistance of some helminth species parasitizing sheep and goats is different for the tested chemical groups. Ivermectin, at 0.2 mg/kg dosage, presented inferior anthelmintic efficacy against some of these parasites. Of these species, populations of Haemonchus contortus, followed by Trichostrongylus colubriformis, Cooperia curticei and Oesophagostomum columbianum, exhibited the greatest resistance to the aforementioned chemical compound, whereas Trichostrongylus axei displayed higher susceptibility to ivermectin. For moxidectin (0.2 mg/kg), 75% of all H. contortus populations were considered resistant to this drug, whereas all populations of T. colubriformis, T. axei, C. curticei and O. columbianum were susceptible. Trichlorfon and albendazole + levamizole + ivermectin were effective against the analyzed nematode populations, except against one strain of H. contortus and one strain of T. colubriformis. All three Strongyloides papillosus populations evaluated were susceptible to the tested formulations, except for moxidectin, as this compound presented low efficacy indices against all populations of this helminth species.
Keywords: Chemical control; Efficacy; Goat nematodiasis; Resistance; Sheep nematodiasis